Manajemen Pengembangan Spiritual Religi di Panti Asuhan An-Nur Medan - Ferdi, Muhammad; Sahputra, Dika (Jurnal Ragam Pengabdian, 2026)
This study aims to describe the management of religious-spiritual development at the An-Nur Orphanage in Medan using the POAC management functions: planning, organizing, actuating, and controlling. A qualitative descriptive approach was employed, with data collected through in-depth interviews, observation, and documentation involving the orphanage head and caregivers. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that religious-spiritual development at the orphanage is conducted systematically and sustainably. In the planning stage, programs feature clear objectives and schedules, although written guidelines remain basic. During the organizing stage, the division of tasks among administrators, caregivers, and religious instructors functions effectively, supported by grouping children based on age and religious understanding. In the actuating stage, guidance is provided through role modeling, the habituation of acts of worship, persuasive motivation, and the creation of a religious environment. In the controlling stage, oversight is maintained through routine monitoring, periodic evaluations, and follow-up training for children requiring additional guidance. In conclusion, the application of POAC functions effectively supports the optimal development of the children's religious character, although program documentation and evaluation instruments require strengthening to ensure management becomes more structured and measurable.